Plant diversity and spatial vegetation structure of the calcareous spring fen in the "Arkaulovskoye Mire" Protected Area (Southern Urals, Russia) - E.Z. Baisheva; A.A. Muldashev; V.B. Martynenko; N.I. Fedorov; I.G. Bikbaev; T.Yu., Minayeva; A.A. Sirin (Mires and Peat, 2020)
The plant communities of base-rich fens are locally rare and have high conservation value in the Republic of Bashkortostan (Russian Federation), and indeed across the whole of Russia. The flora and vegetation of the calcareous spring fen in the protected area (natural monument) “Arkaulovskoye Mire” (Republic of Bashkortostan, Southern Urals Region) was investigated. The species recorded comprised 182 vascular plants and 87 bryophytes (67 mosses and 20 liverworts), including 26 rare species listed in the Red Data Book of the Republic of Bashkortostan and seven species listed in the Red Data Book of the Russian Federation. The study area is notable for the presence of isolated populations of relict species whose main ranges are associated with humid coastal and mountainous regions in Central Europe. The vegetation cover of the protected area consists of periodically flooded grey alder - bird cherry forests, sedge - reed birch and birch - alder forested mire, sparse pine and birch forested mire with dominance of Molinia caerulea, base-rich fens with Schoenus ferrugineus, islets of meso-oligotrophic moss - shrub - dwarf pine mire communities, aquatic communities of small pools and streams, etc. Examination of the peat deposit indicates the occurrence of both historical and present-day travertine deposition. A retrospective assessment of the seasonal development of vegetation and surface temperature at Arkaulovskoye Mire, using earth observation data, suggests that the microclimatic conditions of the mire habitat can mitigate extremes of continental climate in the forest-steppe zone and thus support the survival of the mire’s relict floristic complexes. Finally, a comparison of climatic data between the Arkaulovskoye Mire and Nätsjöbäcken Mire in Sweden, which is a site for Schoenus ferrugineus within its main European range, shows that the annual temperature regimes of these two locations are rather similar.